A self-determination perspective on Chinese fifth-graders' task disengagement. (April 2017) - Zhou, Mingming; Ren, Jing
Engagement in academic tasks is important. However, compared to the large body of research on task engagement, the number of studies on task disengagement is quite limited. The aim of this study is to examine the associations between the motivational (self-determination) and attitudinal antecedents (learning orientations) of task disengagement. The sample consisted of 347 fifth-graders in China. We tested two mediation models that incorporated self-determination (autonomous versus controlled), learning orientation (collaborative versus competitive), and task disengagement among Chinese primary school students in learning English. Results showed collaborative learning orientation mediated the link between autonomous motivation and task disengagement. Collaborative learning orientation was also found to be negatively related to task disengagement.